Role of Transbronchial Lung Cryobiopsies in Diffuse Parenchymal Lung Diseases: Interest of a Sequential Approach - Benjamin Bondue; Thierry Pieters; Patrick Alexander; Paul De Vuyst; Maria Ruiz Patino; Delphine Hoton; Myriam Remmelink; Dimitri Leduc (Pulmonary Medicine)
Background. Transbronchial lung cryobiopsies (TBLCs) are a promising diagnostic tool in the setting of diffuse parenchymal lung diseases (DPLDs). However, no comparison with surgical lung biopsy (SLB) in the same patient is available. Methods. The diagnostic yield and safety data of TBLCs, as well as the result of SLB performed after TBLCs, were analysed in a multicentric Belgian study. A SLB was performed after TBLCs in absence of a definite pathological diagnosis or if a NSIP pattern was observed without related condition identified following multidisciplinary discussion. Results. Between April 2015 and November 2016, 30 patients were included. Frequent complications included pneumothorax (20%) and bleeding (severe 7%, moderate 33%, and mild 53%). There was no mortality. The overall diagnostic yield was 80%. A SLB was performed in six patients (three without definite histological pattern and three with an NSIP). The surgical biopsy changed the pathological diagnosis into a UIP pattern in five patients and confirmed a NSIP pattern in one patient. Conclusion. TBLCs are useful in the diagnostic work-up of DPLDs avoiding a SLB in 80% of the patients. However, surgical biopsies, performed as a second step after TBLCs because of an indefinite diagnosis or a NSIP pattern, provide additional information supporting the interest of a sequential approach in these patients.